2017
DOI: 10.1002/cncr.30649
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of neurofeedback on chemotherapy‐induced peripheral neuropathy: A pilot study

Abstract: BACKGROUND Chemotherapy-induced peripheral neuropathy (CIPN) is a significant problem for cancer patients, and there are limited treatment options for this often debilitating condition. Neuromodulatory interventions could be a novel modality for patients trying to manage CIPN symptoms; however, they are not yet the standard of care. This study examined whether electroencephalogram (EEG) neurofeedback (NFB) could alleviate CIPN symptoms in survivors. METHODS This was a randomized controlled trial with survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 27 publications
2
54
0
1
Order By: Relevance
“…31 However, in our recently published article of the primary outcomes for this study (up to the end of treatment time point), we analyzed changes in brain activity in relation to NFB and in association with pain outcomes and found statistically significant differences over time and between groups within the EEG frequencies and scalp locations we were training. 15 We also explored changes in brain function in regions known to be active with a placebo and concluded that although placebo could be a factor in this study, it was not the only factor leading to improvement in symptoms because placebo brain regions showed activity in both the NFB and WLC groups. 15 Future research would benefit from the addition of a placebo feedback group to control for attention and also to examine brain activity associated with placebo NFB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 However, in our recently published article of the primary outcomes for this study (up to the end of treatment time point), we analyzed changes in brain activity in relation to NFB and in association with pain outcomes and found statistically significant differences over time and between groups within the EEG frequencies and scalp locations we were training. 15 We also explored changes in brain function in regions known to be active with a placebo and concluded that although placebo could be a factor in this study, it was not the only factor leading to improvement in symptoms because placebo brain regions showed activity in both the NFB and WLC groups. 15 Future research would benefit from the addition of a placebo feedback group to control for attention and also to examine brain activity associated with placebo NFB.…”
Section: Discussionmentioning
confidence: 99%
“…15 We also explored changes in brain function in regions known to be active with a placebo and concluded that although placebo could be a factor in this study, it was not the only factor leading to improvement in symptoms because placebo brain regions showed activity in both the NFB and WLC groups. 15 Future research would benefit from the addition of a placebo feedback group to control for attention and also to examine brain activity associated with placebo NFB. Finally, we hypothesize that NFB has distinct effects depending on location of the feedback on the scalp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(42) EEG nörofeedback in değerlendirildiği bir çalışmada ise uygulama haftada 2 kez olacak şekilde toplam 20 seans uygulanmış ve nöropati semptomlarını azaltmada etkili olduğu EEG sonuçlarıyla tespit edilmiştir. (43)…”
Section: Nörofeedback Transkutan Sinir Uyarısı (Tens)unclassified
“…A randomized controlled trial by Prinsloo et al introduces a different approach to the treatment of CIPN using electroencephalogram (EEG) neurofeedback. In this trial, 30 participants with CIPN were randomized to the neurofeedback arm.…”
mentioning
confidence: 99%